Caracterización mecánica de un ligante asfaltico 60/70 modificado con GCR y nanoarcilla. - Rojas Vizuete, Santiago Enrique (2022)
The road maintenance is a fundamental objective all over the world, the subject of nanotechnology is still something new that is trying to be implemented in the Civil Engineering Degree. “THE RECYCLED RUBBER IS A GREAT SOURCE OF RAW MATERIAL THAT HAS BEEN USED IN RECENT YEARS TO INCREASE THE ASPHALT´S RESISTANCE”. Nanoclay is a material of great variety, having unique physical and chemical properties that have been implemented in the construction of asphalt surfaces, these were of great help through optimizing them. Therefore, in this research work, the asphalt mixtures were modified with these two materials to determine some of their mechanical properties and thus better analyze and understand the reaction of the rubber and nanoclay together with a 60/70 asphalt. These two materials had to be used alone with different percentages to obtain the best possible result, the crumb rubber with percentages of 10%, 15% and 20% while the nanoclay with 3%, 5% and 7%. Resulting in a final mixture with 10% crumb rubber and 3% nanoclay. For the analysis of the mechanical properties, penetration, flash point and viscosity tests were carried out. The most notable was the flash point test, where at only 201 °C the modified asphalt had a more accelerated reaction to heat compared to the other samples presented. Similarly, there was an improvement in stiffness and the modified mix maintained the conventional asphalt performance when it came to its viscosity according to Surfax's rheological curve. This project helps us as niche research in order to carry out further testing, specifically with this nanoclay and crumb rubber to determine a deep description of its mechanical properties or to predict how this would react adding other components of a mixture.